(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Fontainville Abbey(1794), by William Dunlap, inspired by Ann Radcliffe’s Romance of the Forest(1791), is a play that has been relegated to oblivion. Dunlap is considered an outstanding historian, as well as the first American playwright and the first Gothic writer in the country. Forgotten by his peers, Dunlap was also forgotten by the academy. The aim of this article is to show how Dunlap’s melodramatic dramaturgy and its dialogue with American literature’s seminal texts serve as a receptacle for memory and how this memory, in this case, the memory of the history of American melodramatic (Gothic?) theater, is transformed into phantasmagoria.